Position of the Principle of Good Faith in Life Insurance Agreements Study of Decision No. 489/Pdt.G/2021/Pn.Mdn - Putri, Aprilia; Purwanto, Purwanto; Hediati, Febri Noor (LEGAL BRIEF, 2024)
Insurance is regulated by Law No. 40 of 2014 concerning Insurance. The three main parties involved in insurance are the policyholder, the insured, and the insurer. The basic principle in an insurance agreement is good faith, which refers to mutual trust between the parties. However, disputes often occur regarding the implementation of this principle, such as unilateral policy cancellation and rejection of life insurance claims, which reflect a lack of good faith. This study aims to analyze the position of the principle of good faith in life insurance agreements at PT. Asuransi Allianz Life Indonesia, as well as to consider the legal basis of judges in cases of policy cancellation and claim rejection as stated in Decision No. 489/Pdt.G/2021/PN Mdn. The approach used is doctrinal research, focusing on the analysis of legal norms, including relevant legal theories and principles. The results of the study indicate that the principle of good faith in life insurance agreements at PT. Allianz Life Indonesia is based on trust between the insurer and the insured to reach a fair and transparent agreement. If this principle is ignored, disputes cannot be avoided. In his decision, the judge did not specifically refer to the Insurance Law or the Civil Code, but based his decision on the trial facts and evidence provided by the parties.